Chemical characteristics for optimizing CYP2E1 inhibition. (5th December 2015) - van de Wier, B.; Balk, J.M.; Bast, A.; Koek, G.H.; Haenen, G.R.M.M.
Abstract: Cytochrome P450 2E1 (CYP2E1) expression and activity in the liver is associated with the degree of liver damage in patients with alcoholic steatohepatitis (ASH) as well as non-alcoholic steatohepatitis (NASH). CYP2E1 is known to generate reactive oxygen species, which leads to oxidative stress, one of the hallmarks of both diseases. Apart from ROS, toxic metabolites can be formed by CYP2E1 metabolism, further potentiating liver injury. Therefore, CYP2E1 is implicated in the pathogenesis of ASH and NASH. The aim of this study was to determine the chemical characteristics of compounds that are important to inhibit CYP2E1. To this end, structurally related analogs that differed in their lipophilic, steric and electronic properties were tested. In addition, homologues series of aliphatic primary alcohols, secondary alcohols, aldehydes, ketones and carboxylic acids were tested. It was found that inhibition of the CYP2E1 activity is primarily governed by lipophilicity. The optimal log D7.4 (octanol/water distribution coefficient at pH 7.4) value for inhibition of CYP2E1 was approximately 2.4. In the carboxylic acids series the interaction of the carboxylate group with polar residues lining the CYP2E1 active site also has to be considered. This study sketches the basic prerequisites in the search for inhibitors of CYP2E1, which would strengthen our therapeutic armamentarium against CYP2E1 associated diseases, such as ASH and NASH. Highlights: CYP2E1 inhibitors might be used in the treatment of ASH and NASH. Lipophilicity is the major chemical characteristic determining CYP2E1 inhibition. Carboxylic groups interact with polar residues lining the CYP2E1 active site.